Impact of a fall in the elderly: an analysis of the risk factors - Deivson Wendell da Costa Lima; Alyne Mara Maia Cruz; Fabíola Maria Pitombeira de Morais; Arthur Dyego de Morais Torres; Maria Célia de Freitas (Rev Rene)
One aimed to identify the risk factors associated to falls in the elderly, which reflect on their quality of life. This is a descriptive, cross-sectional study. A questionnaire was used to collect data from older adults of an active living group from Russas-CE during the period from August to December 2011. The data were inserted in electronic spreadsheets, analyzed by the descriptive statistics and submitted to odds ratio and chi-square tests with significance level p<0.05. The results indicate a high prevalence of falls in the elderly, especially women (OR:14.636; CI- 2.82-75.954). The intrinsic significant factors were hearing problems (p=0,02) and foot problems (p=0,01). The extrinsic factors were steps in the door (17%), resulting in fractures of the upper limb (69%), morbidity (41%) and psychological complaints (70%). Therefore, it is necessary the development of preventive and rehabilitation actions, ensuring a better quality of life for the elderly.